The Improvement of Teachers’ Ability in Managing The Teaching and Learning Process through The Implementation of Academic Supervision with a Collaborative Approach at MTsN 3 West Aceh - Khalil , Almunawar (LUMBUNG AKSARA, 2022)
This study aims to determine the improvement of teachers' abilities in managing the teaching and learning process through the implementation of academic supervision with a collaborative approach at MTsN 3 West Aceh Semester 1 of the 2022/2023 Academic Year. The research conducted wasan action research. The method and the design of this action research was carried out with research procedures based on the principles of Kemmis and Taggart (1988:10) which included the following activities: (1) planning (planning), (2) implementing action (action), 3) observation (observation). ) , (4) reflection (reflection). The research subjects were teachers of MTsN 3 West Aceh Semester 1 for the 2022/2023 academic year with a total number of teachers was 8 teachers. Data collection techniques used were an observation and documentation studies. The validity of the data using triangulation, namely the triangulation used in the study is triangulation of data sources and triangulation of methods. Data analysis used was qualitative analysis. The results showed an increase in the ability of teachers in the management of the teaching and learning process, where in the initial conditions there were no teachers who were able to arrange the management of the teaching and learning process properly, this was evidenced by the low average score obtained by the teachers. namely 49.50 and only included in the LESS category, in the first cycle it increased significantly and there were 3 teachers or 37.50% who were declared capable of managing the teaching and learning process well, with a classical average score of 66, 83 and included in the ENOUGH criteria and in the last cycle became a teacher or 100%, as evidenced by the classical score of 80.17 in the GOOD score criteria. From the results of the research as described above, it can be concluded that the implementation of academic supervision with a collaborative approach at MTsN 3 West Aceh Semester 1 of the 2022/2023 Academic Year can improve teachers’ skills in managing teaching and learning process.